If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 9X = 86 Solving 14 + 9X = 86 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 9X = 86 + -14 Combine like terms: 14 + -14 = 0 0 + 9X = 86 + -14 9X = 86 + -14 Combine like terms: 86 + -14 = 72 9X = 72 Divide each side by '9'. X = 8 Simplifying X = 8
| 6x^2-8x+5=0 | | 9X+2X=33 | | (b)3=-4 | | b+6b-4b+1=22 | | b+6b-4b+1=23 | | b+6b-4b+1=24 | | (M)-7=-7 | | -3y+2x=-28 | | 2x^3+2x-48=0 | | 12x-9= | | x^2+4y^2=1 | | 3a+9b-3a-b= | | m+(-9)=12 | | (2x+5)(2x+5)=25 | | (2x+5)2x+5=25 | | 98(x)-x^2-7.96=0 | | 2a^2-98=0 | | x^2=21+5x | | 0=-50x-2x^2 | | (x+2)(x)(2)=70 | | -4(2x-3)=7(x+8) | | (X)-9=10 | | -3x=9x^2 | | 5x^2-2x-39=0 | | -10=-14v+15v | | 14t-8=6 | | 7[m-3]=7 | | e=825+3.25n | | (C)4=6 | | (C)+7=12 | | 1.7(5-x)=1.5(3-x) | | 9m^2+16=0 |